SISTEM INFORMASI PENYULUH PERTANIAN DAN KELOMPOK TANI DI BALAI PENYULUH PERTANIAN MANOKWARI BARAT MENGGUNAKAN FRAMEWORK LARAVEL 9 DAN BOOTSTRAP 4.6 : AGRICULTURAL EXTENSION AND FARMER GROUP INFORMATION SYSTEM AT THE WEST MANOKWARI AGRICULTURAL EXTENSION CENTER USING THE Laravel 9 AND BOOTSTRAP 4.6 FRAMEWORKS - Natalia Christi Rumbarar; Julius Panda Putra Naibaho; Marlinda Sanglise (JISTECH: Journal of Information Science and Technology, 2025)
This study discusses the design of a web-based information system utilizing Laravel 9 and Bootstrap 4.6 for the West Manokwari Agricultural Extension Center (BPP). This system aims to optimize information management, increase public access, and accelerate data management. The research method uses a waterfall approach with stages of requirements, design, implementation, verification, and maintenance. The main features developed include managing extension schedules, farmer group data, work area data, and agency profiles. Testing using black-box testing shows that all functions run as required. This system is expected to improve the efficiency, transparency, and accountability of data management within the West Manokwari BPP.